Prolonged postoperative ileus in a patient with primary pneumatosis cystoides intestinalis: a case report - Hiroshi Tamura; Tatsuo Kanda; Tadasu Chida; Hitoshi Kameyama; Ukihide Tateishi; Toshifumi Wakai; Makoto Naito (Surgical Case Reports)
Abstract Background Pneumatosis cystoides intestinalis (PCI) is a rare disease characterized by multiple gas-filled cysts in the intestinal wall and is associated with various comorbidities. We report herein a case of intractable paralytic ileus caused by primary PCI. Case presentation A 73-year-old man visited out hospital complaining of abdominal pain and vomiting. He had been hospitalized twice for intestinal obstruction in the past 2 months. Based on his history of appendectomy, mechanical bowel obstruction caused by adhesion was diagnosed, and the patient underwent surgery. However, laparotomy revealed small bowel dilatation despite the absence of obstruction or stenosis. Multiple nodules were found in the wall of the dilated bowel loops. The dilated jejunum was excised. Histological examination revealed that the nodules were small gas-filled cysts, suggesting PCI. We made a diagnosis of ileus with underlying PCI and managed the patient conservatively. A large amount of nasogastric tube drainage continued for a long period postoperatively. The patient underwent relaparotomy 35 days after the first operation. The upper jejunum was markedly dilated, although no mechanical stenosis was found. The atonic, dilated jejunum was excised and the ileal stump was anastomosed to the duodenum in a double tract fashion. The patient underwent hyperbaric oxygen therapy because the ileus persisted postoperatively. His condition gradually improved and he was discharged 53 days after the second operation. Conclusions Non-operative treatment is recommended for primary PCI of unknown etiology. Surgeons should be mindful of the possibility of primary PCI when considering surgical intervention for patients with bowel obstruction.